When is a State Predatory? - James A. Robinson (Center for Economic Studies and ifo Institute (CESifo), 1999)
I argue that whether or not a state is predatory hinges on the relationship between development and the distribution of political power in society. Development is typically inconsistent with the preservation of the political status quo and this gives those who initially hold political power an incentive to oppose it. I show that, contrary to the conventional wisdom, the likelihood of predatory behaviour may be positively related to the extent to which a regime is encompassing and values the future. The model also predicts that the lower is the level of income, and the more unequal is society, the more likely the state is to be predatory. Initial inequality, since it influences the likelihood of political transition, is a crucial determinant of policy choice. I also show how factor endowments influence policy: states in economies relatively endowed with natural resources, or where the elite's wealth is concentrated in land, are more likely to be predatory.
Keywords: 330; development; political economy; autocracy; democracy